A Rare Cause of May-Thurner Syndrome Postarterial Intervention - Chan, Hiok Yang; Choke, Edward Tieng Chek; Tang, Tjun Yip; Sivanathan, Chandramohan; Jasmine, Chua Ming Er; Kumar, Pradesh (Journal of Clinical Interventional Radiology ISVIR, 2019)
May-Thurner syndrome (MTS) is rare condition thought to occur due to an anatomical variation. In MTS, there is left iliac vein compression by the right iliac artery and lumbar spine resulting in left lower limb deep venous thrombosis. The authors report a rare cause of MTS postarterial intervention. They describe the unusual case of an Asian man who presented with acute left lower limb deep venous thrombosis 5 days following left common iliac artery angioplasty and stent insertion. Computed tomographic (CT) venogram demonstrated the left iliac vein compression by the left iliac artery stent. Successful recanalization of the thrombosed iliac vein was achieved with a combination of pulse spray thrombolysis and rheolytic mechanical thrombectomy, followed by angioplasty and stent placement in the iliac vein. There was rapid and complete resolution of symptoms. This report illustrates the use of complementary imaging modalities and a multidisciplinary team approach to achieve a successful technical and clinical outcome following an unusual case of MTS postarterial intervention and the subsequent successful endovascular management.
Keywords: May-Thurner syndrome; stent; thrombolysis